An Alternative Architecture for Ginga - Zambrano, Arturo; Zubimendi, Juan Antonio; Búcar, Javier (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
The GingaNCL reference implementation is developed by PUC-Rio as a GPL project. This implementation runs on an x86 Linux virtual machine. The reference implementation is an excellent tool for communicating the intended behavior of Ginga but it is diffcult to use it as the software running inside DTV dedicated platforms such as: set-top-boxes or integrated TV-sets. There are two main issues that make it hard to port GingaNCL to dedicated platforms. First, GingaNCL has a monolithic structure that includes functionality usually provided by DTV dedicated platform such as: channel tuning, volume control and user menus. Second, the GPL license forces developers to make the changes available back to the community. This paper presents a refactoring to GingaNCL that addresses the issues stated before by separating the tuning functionality, transport stream and data carousels processing on a different process and by de ning an API between GingaNCL and the dedicated platform.